An Integrated Accounting Matrix for Canada and the United States - Cohen, Jacob; Husted, Steven (American Economic Review, 2016)
In the past two decades, considerable progress has been made in studying the economic relationships between countries through the linkage of large-scale national econometric models. Examples of these projects include Project Link, the RDX2-MPS experiments of the Bank of Canada, and the multicountry model of the Federal Reserve Board. While these models tell us much, they typically suffer from several important problems. First, the linkages are often incomplete. In some cases the separate country models may only be linked via the trade accounts. Or, if capital and factor flows are considered, they are modeled in only a highly aggregated fashion. Second, as Ray Fair (1979) has noted, no model does an adequate job of linking the underlying sectoral flows of funds accounts with the national income accounts. Therefore, in the interest of modeling aggregate relationships, underlying balance sheet constraints may be violated or ignored. This could have, Fair argues, important consequences for empirical results.' In this paper we suggest our own strategy for modeling the economic linkages between any two countries. Our strategy focuses on the underlying flows between these two countries and the sectoral contributions to these flows. That is, we propose to merge the flow of funds accounts via their bilateral balance of payments. We envision an integrated flow of funds accounting framework with the two countries sharing a common balance of payments. This modeling strategy has several advantages. First, our suggested framework could be used, following the strategy of Fair, to supply the financial underpinning for future economic modeling of international linkages of prices and interest rates. The balance sheet constraints inherent in the framework will impart additional information in any statistical estimation of such a model. Second, this strategy should yield a better understanding of a country's balance of payments since it necessarily links domestic decision making with its international outcome. Third, our framework should be useful to policymakers since it would allow them to model the underlying financial implications of proposed policy changes. Finally, the implementation of our proposal could lead to improved accuracy in balance of payments statements. tDiscLussant: John A. Sawyer, University of Toronto.